PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI INFORMASI (TI) TERHADAP HASIL BELAJAR SISWA KELAS XI DI SMK LABOR BINAAN FKIP UNRI PEKANBARU - Saputra, Ridwan Ary; Suarman, Suarman; Hendripides, Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Absract:This study aims to determine the effect of the use of information technology (IT)-based learning media in Vocational School of Labor fostered by FKIP UNRI Pekanbaru. The population and sample in this study were students of class XI with a sample of all students with a total of 72 students, while collectingdata was done by distributing questionnaires to respondents. This study uses a quantitative method with a descriptive approach. Based on the results of the study, it is known that the use of information technology-based learning media is very effective asa medium for learning in the classroom. This is because information technology-based learning media can provide meaningful learning experiences for students, can increase student learning motivation, the media used are in accordance with learning objectives, and can provide an overview of concepts and realities so that they can help students understand learning correctly. Based on the results of the linearity test, it is known that the Deviation from linearity value is 0.560 > 0.05. So it can be concluded that there is a significant linear relationship between the use of information technology-based learning media (X) and student learning outcomes (Y).KeyWords:Use of Learning Media, Learning Outcomes, IT-based Media